A Review of Disciplinary Punishments in Educational Institutions in Light of Islamic Principles - Junaidullah khan; Dr Muhammad Fakhar ud din (Journal of Religion and Society, 2025)
The paper is a scholarly account of the concept of disciplinary punishments of Islamic ShariA consequentially. The main purpose is to discuss the philosophy of punishment in Islam, the goals of it, the constraints, and the use of it in the modern context. According to the Islamic beliefs, punishment is not intended to be vindictive and a source of pain but a form of reform, moral training, justice and social order. Clear directions can be found in the Quran and Sunnah in this respect. The principle, the purpose of Shari*ah is to seek well and avoid evil” points to the fact that all punishments must have a basis in the good of the people and their restoration and not in inhumanity. The study also contains historical evidence, especially the way disciplinary laws used to be put in the period of the Rightly Guided Caliphs. A famous instance is what Caliph Umar (RA) did namely the suspension of the practice of ḥadd (set punishment) based on theft during famine, taking into account the circumstances of the defendant. Moreover, the paper provides the description of the forms of ta zir (discretionary punishments): those whose application is fixed yet the scope is arbitrary, and those that leave the full discretion of the judge, including the light physical punishment, verbal admonition, or monetary fines, especially in educational and training environments.Use of disciplinary measures in learning institutions is a sensitive but important topic and in this regard, the intention, the way and the sensitivity of the teacher to the psychological status of the learner should be taken into serious considerations. The paper cites Prophetic traditions, the utterances of the companions and successors, and the opinions of modern world educationists in making an argument that within proper limits, disciplinary measure in the name of moral education and order is allowed by the Shari-ah. The paper comes to the conclusion that it is not only permissible but an effective means to move society towards becoming a better one that the disciplinary punishment may be used to rehabilitate wrongdoers as long as it is applied with a pure motive of reforming an individual and without conflict to the principles of Shari, as long as pedagogical ethics considerations form the basis. Keywords: Disciplinary punishments, Ta‘zīr, Moral and behavioral reform, Educational institutions, Islamic law, Shari‘ah principles, Maqāṣid al-Sharī‘ah (Objectives of Shari‘ah)